PROBLEMATIKA PEMBUKTIAN PELECEHAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI PASCA PENGESAHAN UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL - Bernadetta Melvina Faustina (2023)
Pressure from the people who feel the need for detailed regulations regarding sexual violence has prompted the government to immediately pass Law Number 12 of 2022 concerning Crimes of Sexual Violence (TPKS Law). The regulations for conducting evidence in the TPKS Law are considered to be able to ease the burden on the victim in providing evidence both during the investigation process and when the case is submitted to trial. This research was compiled using a normative juridical research type and using a statutory approach. The results of this study stated that there were obstacles experienced by victims in the process of proving cases of acts of sexual harassment, especially victims who received acts of sexual harassment in the college environment. In this case the Ministry of Education, Culture, Research and Technology issued a regulation regarding the prevention and handling of sexual violence which required every university in Indonesia to form a Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) to assist all college citizens when they encounter acts of violence. sexual intercourse while inside the campus environment or outside the campus environment while related to college students. The PPKS Task Force does not have high enough authority to resolve a case of sexual violence, so if the victim wants the case to be processed in court, the PPKS Task Force will assist the victim by asking the authorities for assistance for further processing. Keywords: Sexual Harassment, Evidence, Unit for Prevention and Handling of Sexual Violence